Effects of cisplatin on photosensitizer-mediated photodynamic therapy in breast tumor-bearing nude mice - Tae-Gyu Ahn; Ji Min Jung; Eun-Jeong Lee; Ji Hyun Choi (Korean Society of Obstetrics and Gynecology, 2019)
ObjectiveThis study aimed to evaluate the potential effects of cisplatin on photodynamic therapy (PDT) in breast cancer using a breast tumor-bearing mouse model.MethodsIn this study, breast tumor (experimental mammary tumour-6 cell)-bearing nude mice were used as experimental animals. Photolon® (photosensitizer, 2.5 mg/kg body weight [BW]) was injected intraperitoneally; after 2 hours, the tumors were irradiated (660 nm, 80 J/cm2) using a diode laser tool. Cisplatin (3 mg/kg BW) was injected intraperitoneally 1 hour before the Photolon® injection.ResultsTumor volume increased over time in the control group and was not different from that in the cisplatin group. In the PDT group, the tumor volume increased on day 3, but not on day 7. In the cisplatin+PDT group, tumor volume increased on day 3 but decreased on day 7. There was no significant difference in the levels of thiobarbituric acid reactive substance (TBARS) in tumor tissues between the control and cisplatin groups. The levels of TBARS in the cisplatin+PDT group were higher (47%) than those in the PDT group. Analysis of tumor tissue transcriptomes showed that the expression of genes related to the inflammatory response including CL and XCL genes increased, while that of Fn1 decreased in the cisplatin+PDT group compared with the PDT group.ConclusionThese results suggest that cisplatin enhances the therapeutic effect of PDT in a breast tumor-bearing mouse model. However, further clinical studies involving patients with breast cancer is needed.